Mexico: «the population explosion» and mass migration - Nadejda Kudeyarova (Ибероамериканские тетради)
The debate over the Mexican migrants issue has been intensi ed by Donald Trump’s election. His harsh statements have provoked a discussion on the US policy for Mexico, as well as on the migration regulation in the United States. However, the mass migration of the last quarter of XX - beginning of XXI centuries may be also readily associated with the social and demographic processes developed in Mexico throughout the 20th century. The dynamics of migratory activity followed the demographic changes. The internal causes of the Mexican migration analysis will allow more clarity in understanding contemporary migration interaction between the two neighboring countries.